ANALISIS PENGARUH FAKTOR LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA USAHA PENJUALAN SEPEDA MOTOR BEKAS DI KECAMATAN PURWOKERTO SELATAN KABUPATEN BANYUMAS - P Edi Sumantri; Kundaru Hadiyato (Majalah Imiah Manajemen & Bisnis, 2020)
Workers or employees must be well managed to be able to deal with increasingly intense competition conditions. Work environment and compensation are considered as important factors in determining employee job satisfaction. In this research, both of these factors will be seen to influence the employee job satisfaction of the sales force in the small business engaged in the sale of used motorcycles Two hypotheses proposed in this study are: there is a significant influence between work environment factors and compensation on employee job satisfaction; and compensation is a factor that has a greater effect on employee job satisfaction in small businesses engaged in the sale of used motorcycles. The results of the first hypothesis were accepted, while the second hypothesis was rejected.